Vulvar Lipoma: A Case Report - Reda, Ahmed; Gomaa, Ihab (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
The present study is a case report of vulvar lipoma. The vulva is a rare site for the development of lipomas, and the aim of the study is to determine if the current imaging modalities can diagnose lipomas correctly. A 43-year-old patient presented with a painless, slowly progressive, oval, mobile and non-tender right vulvar mass compressing the vagina and totally covering the introitus. Both the ultrasonography and magnetic resonance imaging (MRI) exams suggested the diagnosis of lipoma. Surgical excision was performed, and the histopathological examination of the mass confirmed a lipoma.
Keywords: benign tumor; lipoma; mesenchymal tissue; soft tissue; vulva; vulvar lipoma